Reviews DVD/Blu-ray. Issue 3 (1st September 2014) - Gates, Brendan; Martin, Richard F.; Mayo, Jonathan; Rasberry, Margaret; Warpole, Kailyn N.
Laurence AnywaysLaurence Anyways (2012) CanadaDirector Xavier Dolan Runtime 168 minutesDVD USA, 2013 Produced and Distributed by Alliance Viva Film (region 1)The KillingThe Killing (1956) USA Director Stanley Kubrick Runtime 84 minutesBlu-ray USA, 2011 Produced and Distributed by The Criterion CollectionA Look into the World of Independent GamingIndie Game: The Movie (2012) USA Director Lisanne Pajot and James Swirsky Runtime 94 minutesDVD USA, 2008 Produced and Distributed by Blink Works Media (region 1)Jules et JimJules et Jim (1962) France Director François Truffaut Runtime 105 minutesDual Format Blu-ray/ DVD USA, 2013 Produced and Distributed by The Criterion Collection (region 1)A Brief History of Time in 11 FramesA Brief History of Time (1991) UK/Japan/USA Director Errol Morris Runtime 84 minutesDual Format Blu-ray/DVDUSA, 2014 Produced and Distributed by The Criterion Collection (region A/1)